Video-assisted thoracoscopic surgery in the management of malignant pleural disease - Luciano, Giulia; Waller, David A. (Video-Assisted Thoracic Surgery, 2018)
Surgical treatment of malignant pleural diseases is usually indicated in advanced disease with a limited prognosis. associated with significant morbidity. Minimally invasive approaches must be offered as first line treatment since they reduce chest wall trauma, preserve respiratory muscle function and therefore expedite recovery. Most of the evidence for therapeutic video-assisted thoracoscopic surgery (VATS) pleural surgery is for primary malignant pleural mesothelioma (MPM) whilst in the treatment of metastatic non-small cell lung cancer (NSCLC) therapeutic VATS is concerned mainly in the prevention of pleural effusion or the treatment of malignant empyema. An increasing amount of management decisions using VATS in malignant pleural disease is evidence-based. There have been and continue to be well constructed clinical trials of the various potential therapeutic applications of VATS in this context. VATS allow for therapeutic manipulation of the pleural environment including dissection techniques aimed at symptom control by direct tumour debulking. We will consider the role of VATS in the management of malignant pleural disease in the context of a lung that will expand; when the lung is entrapped and when the lung is entrapped by a malignant empyema. In the first scenario the therapeutic choice is between simple VATS administration of chemical pleurodesis or the more controversial subtotal parietal pleurectomy. When the lung is entrapped but the cavity still cleans the choice is between the insertion of an indwelling pleural catheter (IPC) or the highly disputed VATS visceral pleurectomy to re-expand the lung. When a malignant effusion becomes infected the entrapped lung may form a malignant pleural empyema and the debate is between just debridement or the more technically challenging decortication. We will attempt to evaluate all of these procedures and formulate a management algorithm.